Deviation of Enhancing Stereotypes through Lexicalization and Songs in Mulan - Sanita, Joan (Journal of Language and Literature, 2015)
This paper investigates the deviation of enhancing stereotypes that takes place in Disney film Mulan. It attempts to reveal the stereotypes that arise from the film in terms of lexicalization and the songs. Also, this study examines the implication of watching this type of movie as it is classified as family genre. The analysis is based on S. Jager and F. Mayer (2009) film analysis on Foucauldian approach of discourse analysis. It connects linguistic discursive practice, non-linguistic discursive practice, and materialization (object). Because of the limitation of the space in presenting the data, this paper focuses only on the linguistic discursive practice in terms of lexicalization and four songs represented in the film. The result shows that in terms of lexicalization, the use of word ‘girl’ compared ‘man’ has an implied deal with the case of stereotypes. Likewise, the symbol of ‘girl’ as a doll and ‘man’ as a sword symbolized in the film also bring the effect on the stereotypes which are characterized by the female and male characters. Then, in terms of songs, the four songs that are sung in the film also convey the stereotypes which can be denoted by the film.